2015
DOI: 10.3945/ajcn.114.098988
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain ω-3 fatty acid intake and endometrial cancer risk in the Women’s Health Initiative

Abstract: Long-chain ω-3 intake was associated with reduced endometrial cancer risk only in normal-weight women. Additional studies that use biomarkers of ω-3 intake are needed to more accurately estimate their effects on endometrial cancer risk. This trial was registered at clinicaltrials.gov as NCT00000611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
2
20
1
Order By: Relevance
“…Inverse associations are not supported by previous studies, which have found no associations between intakes of these fatty acids and risk of endometrial cancer (16,17,29).…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…Inverse associations are not supported by previous studies, which have found no associations between intakes of these fatty acids and risk of endometrial cancer (16,17,29).…”
Section: Discussioncontrasting
confidence: 45%
“…However, in the VITAL Study, we reported 175% linear increases in endometrial cancer risk among overweight/obese women (16) which were not subsequently replicated in the much larger WHI (17). In each study, associations reported for fish intake (especially baked or broiled fish) were similar to those reported for the LC ω-3 PUFAs.…”
supporting
confidence: 64%
See 3 more Smart Citations